PEMANFAATAN MEDIA SOSIAL SEBAGAI KEGIATAN KEHUMASAN PERPUSTAKAAN IPDN JATINANGOR - Sardi, Auliya Noviyani (Jurnal Teknologi dan Komunikasi Pemerintahan, 2021)
Social media is often used by people as a place for exchanging information. The applicability of social media can be used as a medium for public services, for example publicity and services of a library. The library of IPDN Jatinangor already has social media, but it has not been used optimally. The publicity is still conducted directly or via instant messengers by an individual. The purpose of writing this article is to contribute to the use of social media as a mean of public relations, especially in the field of libraries. The method used in this article is action research modeled by Kemmis and McTaggart. The approach used in this research is a qualitative approach with data collection techniques such as documentation, short interviews, and observations. There are also social media that are used, namely Instagram, Facebook and Youtube. This utilization gets positive feedbacks from actual and potential users, as well as wider community. This result is proven by the increase in social media followers of the IPDN Library Unit. The conclusion of this article is that the use of social media as a mean of public relations for libraries can make them be known more widely, facilitate services for users and general public, as well as form a dynamic image for the libraries. Keywords: Library Services, Library Public Relations, Public Services